A Prospective Study of Prevalence of Carotid Artery Disease in Patients with Coronary Artery Disease and its Correlation with Traditional Atherosclerotic Risk Factors in Central India - Umesh Kumar Chandra; Yashwant Panwar; Anil Bharani (International Journal of Cardiovascular Practice, 2019)
Introduction: Early atherosclerosis mainly involves carotid artery, which leads to increased carotid artery intima media thickness (CIMT).The potential value of CIMT improving the predictive capacity of traditional risk factors of CAD is an understudied and underutilized issue. Because of increasing availability of highly sensitive ultrasonography probes and for a noninvasive procedures, we can predict coronary artery disease (CAD) more precisely in patients having multiple traditional risk factors so it may reduce morbidity and mortality due to CAD and elevated CIMT can be used as surrogate marker of underlying CAD.Methods: This study enrolled 250 admitted patients as a case of CAD. The patients were assessed by detailed history taking, thorough clinical examination, measurement of CIMT, blood sugar and lipid level.Results: Carotid artery disease was present in 88 (35%) of 250 CAD patients. All modifiable cardiovascular risk factors were statistically significantly high in patients of CAD with carotid artery disease. In obese, diabetic, hypertensive, dyslipidemia and smoker patients, carotid artery disease was present in 55% (P = 0.00), 41% (P = 0.00), 43% (P = 0.007), 47% (P = 0.002) and 43% (P = 0.003) respectively. CAD patients who had 1 risk factor, 29% were associated with carotid artery disease. Comparison of single risk factor with patients who had no risk factor, there was non-significant correlation for carotid artery disease. CAD patients who had 2, 3, 4 and 5 risk factors, carotid artery disease was present 24 (32%) (p = 0.02), 15 (55%) (P = 0.0003), 17 (61%) (P = 0.00006) and 6 (67%) (P = 0.0008).Conclusion: elevated CIMT can be used as one of the important risk factor for early diagnosis of CAD and to reduce morbidity and mortality due to CAD.